The Role of Teacher-Student Interpersonal Relations in Flipped Learning on Student Engagement - Li, Ruiguang (Frontiers in Psychology, 2021)
Education in essence is an interactive activity in which the teacher and student interactions construct a learning path to raise knowledge. However, it is evident that this learning path is not merely cognitive, and the role of interpersonal relationships should be taken for granted. Teacher-student relationships are among salient factors in effective teaching which trigger students’ achievement, motivation, and engagement (Martin & Dowson, 2009), and student engagement seems like a keystone for educational achievement. One relatively innovation that promotes student engagement and undertakes more effective learning and deeper knowledge of the materials is flipped learning (Kim, 2017). This theoretical review article is written to enlighten scholars, teachers, and learners with key concepts in interpersonal relations and their roles on student engagement in the flipped learning context. Some pedagogical implications with the prospective to edify the practice of teachers, students, and syllabus designers are presented.